Kaempferia parviflora Ethanol Extract, a Peroxisome Proliferator‐Activated Receptor γ Ligand‐binding Agonist, Improves Glucose Tolerance and Suppresses Fat Accumulation in Diabetic NSY Mice. Issue 2 (6th February 2019) - Ochiai, Masaru; Takeuchi, Toshiki; Nozaki, Tsutomu; Ishihara, Ken‐o; Matsuo, Tatsuhiro
Abstract : Abstract: This study assessed the effect of Kaempferia parviflora, also known as black ginger (BG), and its ethanol extract (BGE) on peroxisome proliferator‐activated receptor (PPAR) γ agonistic activity, glucose tolerance, fat accumulation, and lipids‐induced hypertriglyceridemia in mice. PPARγ ligand‐binding capacity in vitro and polymethoxy flavone contents were highly observed in organic solvent extracts. In an animal experiment A, male diabetic Nagoya‐Shibata‐Yasuda mice were divided into five dietary groups and fed each diet for 8 weeks: AIN‐93G diet (low‐fat [LF] diet), high‐fat (HF) diet, HF diet supplemented with 1% BG, HF diet supplemented with 0.19% BGE, and HF diet supplemented with pioglitazone (PPARγ agonist, 3 mg/kg/day) as a PPARγ agonistic positive control. As determined from glucose and insulin tolerance tests, plasma glucose levels were improved in the BG and BGE groups. The BGE extract suppressed fat accumulation in adipose tissues, liver, and muscles without changing the plasma adiponectin level. In an animal experiment B, in order to investigate the effect of BG and BGE on lipid‐induced hypertriglyceridemia, male ddY mice were divided into three test groups: control, BG‐administered group (500 mg/kg), and BGE‐administered group (100 mg/kg). The plasma triacylglycerol level was not different among the groups during the lipids administration test. These results conclude that the BGE extract containing several kinds of polymethoxy flavones showed PPARγ ligand‐binding capacity in vitro and prevented obesity and insulin resistance independent of adiponectin secretion in mice. Practical Application: Kaempferia parviflora, also known as black ginger (BG), is often used as a folk medicine and a functional food material to prevent metabolic syndrome mainly in Asian regions. Here, we have clarified that ethanol extract from BG (BGE) contains several kinds of polymethoxy flavones to show PPARγ ligand‐binding capacity and is an active extract for the improvement of obesity and insulin resistance. The BGE is expected to be applied for functional food materials in health food markets. Also, polymethoxy flavones to show PPARγ ligand‐binding capacity can be generally applied as a physiological active compound of functional food supplements.